FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dwi Septa Aryani; Kusminaini Armin (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
This study aims to determine the magnitude of the effect of return on total assets, debt ratio and current ratio on firm value in the food and beverage sub-sector listed on the Indonesia Stock Exchange partially and simultaneously. The sample used in this  study is the food and beverage sector manufacturing listed on the Indonesia Stock Exchange for the period 2017 to 2020 with a total sample of 10 companies. The results showed that in the statistical F test, the calculated F value of 7.228 > 2.90 was greater than the f table, so return on total assets, debt ratio and current ratio simultaneously affected on firm value. Then the t statistic test where the results of  return on total assets and debt ratio partially affect Price to Book Value while current ratio  has no effect on firm value. For further research, it is expected to add variables that have not been included in this research model as independent variables, because there are still financial ratios and other factors that may also have an effect but are not included in this study.